PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN PROPERTY AND REAL ESTATE YANG TERDAFAR DI BURSA EFEK INDONESIA TAHUN 2011-2015 - Anggraini, Paramita; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine and analyze the effect of capital structure and profitability on stock prices on property and real estate companies listed on the Indonesia Stock Exchange partially and simultaneously. Where the independent variables in this study is the capital structure and profitability while the dependent variable is the stock price. The number of samples in this study were 7 companies with quantitative data types. The data used in this study is secondary data derived from the financial statements of property and real estate companies listed on the Indonesia Stock Exchange in 2011-2015. The results of data analysis using multiple linear regression analysis, t test, F test and coefficient of determination test. From the results of multiple linear regression analysis either partially or simultaneously shows that the variable of capital structure and profitability have a negative and insignificant influence on stock prices in property and real estate companies listed on the Indonesia Stock Exchange.Keywords: Capital Structure, Profitability and Stock Price